Mallomonas cetosa sp. nov. (Synurales, Chrysophyceae)—a new species from the tropics - Sterlyagova, Irina N.; Ignatenko, Marina E.; Lan, Nguyen Thi; Gusev, Evgeniy S. (Phytotaxa, 2025)
Mallomonas cetosa sp. nov. is described from Vietnam based on silica-scale morphology studied by transmission and scanning electron microscopy. The new species is distinguished by the presence of transverse ribs on the posterior flange, an expansion of the basal plate behind the distal part of the dome on collar scales, a “window” with numerous rimmed pores at the angle of the posterior submarginal rib, and polygonal to rounded mesh of the inner reticulation of the secondary siliceous layer. Based on the ultrastructure of the scales, the new species should be assigned to the section Torquatae. The distribution and habitat conditions of the new species were summarised. Mallomonas cetosa sp. nov. was found in 33 localities in 10 provinces in Vietnam.